ANALISIS KEAUSAN SLIDE SHOE BEARING PADA TRUNNION INLET CEMENT MILL - Edy Kristian; Hestiawan, Hendri; Indrizal (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2023)
Slide shoe bearings and trunnion bearings can wear out due to friction and can cause breakdowns that can stop the production rate and cause losses for the company, the reason for researching slide shoe bearings and trunnion bearings is the occurrence of overhaul so that there is damage.The research only focused on slide shoe bearings and trunnion bearings. The working principle of the slide shoe bearing itself is to support the load from the trunnion which rotates continuously, because it always receives frictional loads, it does not rule out the possibility of wear and tear, this is where the damage to the bearing material begins, damage can be in the form of wear or cracks and so on.The cause of wear on the slide shoe bearing is caused by dirt that enters between the slide shoe bearing and the trunnion which only has a gap of 0.11 mm. This is also caused by less regular lubrication.